Capacity of repeated sprints in professional futsal athletes: an analysis of the Tabata protocol - Flávio Ricardo Guilherme; Sérgio Luiz Carlos dos Santos; Miquel Robert I Ferrer (Revista Brasileira de Futsal e Futebol)
Futsal seems to require a high amount of high intensity efforts and the ability to generate repeated sprints justifies the athlete's ability to maintain maximum effort over repeated sprints, a feature that is indispensable for the sport.  Objective: to evaluate the ability of repeated sprints (TSR) in futsal players in an analysis considering the Tabata training protocol.  Materials and Methods: Cross-sectional p, composed of nine athletes from a futsal team from Paranavaí, Paraná, Brazil who was currently competing in the silver series (second division) of the state championship. Only players who act on the line are selected.  Aerobic capacity was evaluated by the intermittent 30:15 test and the after 48 h, the athletes were recruited to perform the Tabata protocol of high intensity interval training, which originally consists of eight sprints of 20 seconds at 170% of the maximum vVO2, interspersed by 10 seconds of passive recovery.  In each sprint, the subjective perception of exertion (PSE), speed and percentage of the maximum vVO2 were noted.  Results: The reported PSE values by the athletes increased with each sprint performed, and all athletes finished with maximum perception of effort.  Another important data shows that five of the nine athletes evaluated, managed to perform only the first sprint in the intensity of the protocol, so the final average of the percentage of the maximum vVO2 was 121.96 ± 9.32 %.  Conclusion: Professional futsal players were not able to perform the Tabata training protocol at the intensity proposed by the author (170% maximum vVO2), as well as had significant loss in running speed and significant increases in PSE, with 100% of the players reported maximum effort at the end of the protocol.